TREASURE ISLAND - ROBERT LOUIS STEVENSON (PAKISTAN OXFORD UNIVERSITY PRESS, 2019)
When Jim Hawkins sets sail, searching for buried treasure and adventure, he finds himself caught up in a deadly mutiny where he must outwit the cunning pirate Long John Silver in order to stay alive